Application of a Simple Microfluidic Chip Analysis Technology to Evaluate the Inhibitory Role of Protocatechuic Acid on Shear-Induced Platelet Aggregation. (19th May 2021) - He, Cui; Yu, Lihua; Dan, Wenran; Deng, Surong; Ma, Haidong; Liu, Beizhong; Li, Yuan
Abstract : This study aimed to develop a simple microfluidic chip analysis technology to study the inhibitory effect of protocatechuic acid on shear-induced platelet aggregation. The microfluidic chip designed in this study simulates 80% fixed narrow microchannels. This microchannel narrow model uses the finite element analysis module of the three-dimensional modeling software solidwork to analyze fluid dynamic behavior. Blood treated with protocatechuic acid at 1, 2, 4, 8, or 16 µ g/mL was passed through the microchannel stenosis model at a shear rate of 10, 000 s −1 . The platelet adhesion and aggregation behaviors were then measured using fluorescence microscopy and observed in real time. Simultaneously, the antiplatelet aggregation effect of protocatechuic acid was analyzed using thromboelastography and photoelectric turbidimetry. The designed stenosis model of the microfluidic chip can produce a gradient of fluid shear rate, and the gradient of fluid shear rate can induce platelet aggregation. Under this model, the degree of platelet adhesion and aggregation increased as the shear rate increased. In the experimental concentration range of 0–8 µ mol/mL, protocatechuic acid exerted a concentration-dependent inhibition of platelet aggregation. In contrast, thromboelastography and photoelectric turbidimetry failed to demonstrate an inhibitory effect. The microfluidic chip analysis technology developed in this study can be used to study the effect of protocatechin in inhibiting platelet aggregation induced by shear rate in vitro. This technology is simple to operate and can be used as a new type of antiplatelet aggregation analysis technology for screening studies of novel potential antiplatelet aggregation drugs.